Passive aerodynamic control of a single-box girder using self-issuing jets. Issue 208 (January 2021) - Yang, Wen-Han; Chen, Wen-Li
Abstract: In this study, wind tunnel experiments were used to evaluate the control effect of self-issuing jets on the aerodynamic characteristics of a streamlined single-box girder. Based on the deck thickness, the Reynolds number was set to 1.17 ​× ​10 5  ​at a zero angle of attack. The time-averaged and fluctuation characteristics of wake velocities, aerodynamic forces, and surface pressures were investigated along the streamwise and spanwise directions. The results indicated that jet slits arranged on the lower inclined panels of a bridge deck can effectively suppress the lift and moment fluctuations, and introduce three-dimensional variations in the wake velocity. The wake velocity profiles exhibit wave-like distributions in the near-wake region along the spanwise direction, and the length of the vortex formation region is elongated by the jet. Furthermore, the frequency along the spanwise direction of the wake decreases considerably. The changes in the near wake affect the upstream flow field around the deck, which reduces and varies the surface pressure along the deck span, resulting in appreciable reductions in the aerodynamic forces. Highlights: Passive jet method is proposed for optimizing aerodynamic performances of a bridge deck. Jet control effect on the deck without and with rails is analyzed. Three-dimensional changes in pressure distributions are focused. Common angles of attack are considered.